Analisis Tingkat Paparan Radiasi Di Area Tiroid Dokter Kardiologi Intervensi Selama Pemeriksaan Diagnostik Percutaneous Coronary Intervention (PCI) Di Ruang Cath Lab RSUD dr Soedarso Pontianak - Valeria Alex; I Made Lana Prasetya; Suhariadi Atmanta (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Analysis of Radiation Exposure Levels in the Thyroid Area of ​​Interventional Cardiology Doctors During Percutaneous Coronary Intervention (PCI) Diagnostic Examinations in the Cath Lab Room at Dr Soedarso Pontianak Hospital, is research related to patient examinations in the Percutaneous Coronary Intervention Diagnostic Room. The main object in this research is the doctor who examines or treats patients in the room. Researchers wanted to see how many doses of radiation exposure were received by officers examining patients. Method: The research used in this research is quantitative methods. Quantitative research is research that emphasizes analysis on numerical data processed using statistical methods. Based on the type of research, this quantitative research leads to analytical (inferential) research, namely analyzing the relationship between variables by testing hypotheses. The object of focus in this research is an Interventional Cardiology doctor, using 30 patients who have received treatment from a doctor in the cath lab room then the data analysis process uses the measurement results from the pen dose, by conducting research for ten days from 10 August 2023 - 17 August 2023 Results: The results obtained from the average value of radiation dose exposure received by Dr. Interventional Cardiology in the Cath Lab Room at Dr. Soedarso Pontianak Hospital while examining 30 patients, were 0 Sv or the equivalent of 0.000 mSv. Based on these results, it was concluded that the PPE used in the cath lab room at Soedarso Regional Hospital was in accordance with applicable regulations. Conclusion: Based on the data that has been analyzed, it can be concluded that the average value of radiation dose exposure received by Dr. Interventional Cardiology in the Cath Lab Room at Dr. Soedarso Pontianak Hospital while examining 30 patients, is 0 Sv, and is equivalent to 0.000 mSv. Based on the average value of the exposure dose received, which is 0 Sv, the PPE used can reduce the radiation exposure received by doctors. The personal protective equipment includes: Hat, Google Glasses, Thyroid, Apron and protective screen used in accordance with applicable regulations can reduce radiation exposure received by cardiology doctors in the cath lab room at Dr Soedarso Hospital Pontianak.